2011
DOI: 10.5402/2011/354642
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Acute Ischaemic Stroke Outcome Using Clinical and Temporal Thresholds

Abstract: Background. Few studies have analysed the natural course of cerebral ischaemia for predicting outcome. We aimed to determine the early clinical findings and the thresholds for deficit severity and symptom duration that make it possible to stratify outcome. Methods. We included 154 patients with transient ischaemic attack or ischaemic stroke. Stroke profiles and neurological status were assessed from onset to 24 hrs, on admission, at 48 hrs, and at discharge. Outcomes were evaluated using the modified Rankin S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
3
7
1
2
Order By: Relevance
“…Other pertinent clinical variables, such as post-intervention ICH, passes with the primary device, final TICI, and pre- and post-procedure mRS and NIHSS also appeared to significantly impact 90-day mRS. Interestingly, none of the time variables between stroke onset and revascularization were significant predictors of 90-day mRS in the current study. This is in contrast to prior studies which demonstrated certain time-related variables in stroke management to be predictors of overall outcome 12–14. Similarly, while our regression analysis did not show IA tPA to be a predictor of functional outcome, a prior study suggested that thrombectomy in combination with intravenous thrombolysis might improve functional outcomes compared with thrombectomy alone 11…”
Section: Discussioncontrasting
confidence: 99%
“…Other pertinent clinical variables, such as post-intervention ICH, passes with the primary device, final TICI, and pre- and post-procedure mRS and NIHSS also appeared to significantly impact 90-day mRS. Interestingly, none of the time variables between stroke onset and revascularization were significant predictors of 90-day mRS in the current study. This is in contrast to prior studies which demonstrated certain time-related variables in stroke management to be predictors of overall outcome 12–14. Similarly, while our regression analysis did not show IA tPA to be a predictor of functional outcome, a prior study suggested that thrombectomy in combination with intravenous thrombolysis might improve functional outcomes compared with thrombectomy alone 11…”
Section: Discussioncontrasting
confidence: 99%
“…The scale is highly weighted toward anterior circulation deficits, including cortical signs and motor function, while posterior circulation deficits, including cranial nerve signs and ataxia, receive fewer points.Thus, NIHSS may not appropriately evaluate the spectrum of posterior circulation-related signs. The study is supported by a study conducted by Denis Sablot et al which concluded that low and high NIHSS are effective positive predictive values for good and poor outcomes 12 . This study is further supported by a study conducted by Gajurel BP et al which concluded that the baseline neurological status as measured by the National Institute of Health Stroke Scale score predicts the functional status at one month after acute ischemic stroke 13 .…”
Section: Discussionsupporting
confidence: 52%
“…Improvement in the estimation of clinical outcomes could result in more specific management of stroke rehabilitation as well as clearer informing of patients and their relatives. Multiple studies have focused on the baseline National Institutes of Health Stroke Scale (B-NIHSS) as a predictor of functional outcome ( 3 8 ), but only some data are available on the evolution of the National Institutes of Health Stroke Scale (NIHSS) in the first 24 h after stroke onset ( 6 , 9 11 ). Different parameters have been described to assess this change in stroke severity: Delta NIHSS (B-NIHSS–24 h NIHSS), relative reduction in NIHSS (RR NIHSS; delta NIHSS/B-NIHSS), and major neurological improvement (MNI; NIHSS of 0–1 or ≥8-point improvement at 24 h).…”
Section: Introductionmentioning
confidence: 99%